Enchanted by Lohans : Osvald Siren's Journey into Chinese Art - Törmä, Minna (Book collections on Project MUSE., 2013)
Finnish-Swedish art historian Osvald Siren (1879--1966) was one of the pioneers of Chinese art scholarship in the West. This biography focuses on his four major voyages to East Asia: 1918, 1921--1923, 1929--1930, and 1935. This was a pivotal period in Chinese archaeology, art studies, and the formation of Western collections of Chinese art. Siren gained international renown as a scholar of Italian art, particularly with his books on Leonardo da Vinci and Giotto. Yet when he was almost forty years old, he became captivated by Chinese art (paintings of Lohans in the Museum of Fine Arts in Boston) to such an extent that he decided to start his career anew -- in a way. He has left his mark in several fields in Chinese art study: architecture, sculpture, painting, and garden art. This study charts Siren's itineraries during his travels in Japan, Korea, and China. It introduces the various people in those countries as well as in Europe and North America who defined the field in its early stages and were influential as collectors and dealers. Since Siren was a theosophist, the book also explores the impact of theosophical ideas in his work.